Պատկեր, գիր, անուն. Հին Եգիպտոսի դիմապատկերների շուրջ - Գալստյան, Արմինե
Portraiture is the most important and productive genre of Egyptian art. Private portraiture of Old Kingdom is self-thematization of an individual subject. But, surely, the ancient portraits are not self-portraits in our sense of the term. Representation of human face is closely linked to Egyptian ideas of immortality, selfeternalization and self-monumentalization. These are notions of self which seems to determine ancient portraiture’s functional contexts to the greatest extent. The current study investigates how these notions are linked to conceptions of the self and how these conceptions are translated into forms of artistic expression in private portraiture. Here is clarified and talked over the problems of individualization, canon, symbol, form and image. Портрет является наиболее важным и продуктивным жанром древнеегипетского искусства. Частный портрет Древнего Царство тесно связно с ростом индивидуалистических тенденций. Конечно этот первый опыт познания личности через форму олицетворения имет мистический характер и связн с идеей бессмертия и увековечивания индивидума. Данное исследование показывает, каким образом древние представления о человеке интерпретируются в египетских портретах. Здесь обсуждаются проблемы индивидуализации, канона и символа, формы и образа.
Keywords: Արվեստ; Եգիպտոս